'Getting to [un]know you': opening up constructions and imaginations of youth. Issue 6 (2nd November 2017) - Stiegler, Sam
ABSTRACT: This paper rethinks education's reliance on knowing who queer and trans youth are. It suggests that both desires to 'know' who youth are and the processes by which curriculum, policy, and scholarship come to know what is thought to be known about youth flattens and diminishes youths' life experiences and what they might be/come. By examining the ideas that are thought to be known about queer and trans youth, the paper explores how these ideas tend to excise the specifics of youths' lives, particularly along racial lines. Moreover, this paper considers how queer and trans adults' desires to place queer and trans youth within historical lineages, present-day conundrums, and future imaginings limits youths' own explorations and determinations of their own gendered and sexual presentations, expressions, and identities. In total, this paper asks: how might we get to unknow queer and trans youth?